1982
DOI: 10.1002/pssb.2221130215
|View full text |Cite
|
Sign up to set email alerts
|

Comments on the Behaviour of the Absorption Edge of Cd1−xMnxTe for x > 0.4

Abstract: A pinning of the absorption edge of Cdl-,Mn,Te occurs for x > 0.4. Some authors have attributed this behaviour to a transition within the 3d5 localized levels of the Mn2+ ions. The possibility is analysed to observe such a transition in CdMnTe. A comparison with observations on spectra of various substitutional impurities of the 3d series on 11-VI crystals leads to the determination of an upper limit for the crystal field parameter Dq of the Mn atom in CdMnTe crystals and consequently to a lower limit for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…n=O where E"(k) is the band energy for crystals formed from the different nearest-neighbour configurations that can occur in alloys. Theoretical research [20] showed that the alloy band structure calculated according to (8) is in good agreement with experiment with regards to the valence bands and band gap bowing than that of usual treatments of alloys using the VCA and coherent potential approximation (CPA) [20]. As seen from ( 7), the n = 2 ordered structure possesses the largest probability at x = t .…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…n=O where E"(k) is the band energy for crystals formed from the different nearest-neighbour configurations that can occur in alloys. Theoretical research [20] showed that the alloy band structure calculated according to (8) is in good agreement with experiment with regards to the valence bands and band gap bowing than that of usual treatments of alloys using the VCA and coherent potential approximation (CPA) [20]. As seen from ( 7), the n = 2 ordered structure possesses the largest probability at x = t .…”
mentioning
confidence: 65%
“…The anomaly in the absorption edge occurs at large Mn-composition withx ranged between 0.5 to 0.7, the change of rlsv( pd) with composition is too small to measure [23] in comparison to that of Tl,(s). This might possibly be the reason why the absorption edge is almost concentration independent at large Mn-composition as found in [8]. However, at higher Mn-composition, the quick increase in AEPd with increasing pressure would result in a quick upward shift in rlSv( pd) as compared with that of the lower composition, and then a lower absorption edge and a larger negative pressure coefficient should be expected with increasing the composition under pressure.…”
mentioning
confidence: 79%
See 1 more Smart Citation